Enhancing application design for integrated evaluation through user-centered prototyping with figma - Tiana, Ade Hikma; Prasetyo, Rizky Tito; Yulistiawan, Bambang Saras; Masruriyah, Anis Fitri Nur (Institute of Computer Science (IOCS), 2025)
This study developed an integrated evaluation application using a User-Centered Design (UCD) approach combined with user-centered prototyping via Figma, aiming to improve academic service management in educational institutions. The application focused on four main features: service request submission, complaint reporting, lecturer evaluation, and a knowledge base for self-service solutions. Requirements were gathered through questionnaires and interviews with students, lecturers, and faculty leaders to ensure the design met user needs. The prototype was iteratively refined based on quantitative and qualitative evaluations using Likert scale questionnaires. Results showed high user satisfaction with an average score of 4.41, indicating excellent usability, visual appeal, and feature relevance. Thematic analysis highlighted key themes of ease of use, interface consistency, and system security. The integrated UCD and Figma prototyping approach proved effective in producing an adaptive, interactive, and user-friendly application design that supports continuous improvement in academic services.